Roofing Distributor Employee Perception: Workforce Attraction/Retention and Need (Construction Economics and Building, 2023)
Workforce attractions and needs development are present at all levels of the construction industry, from general contractors down to trade contractors and their distributors. Specifically, the roofing industry faces a severe decline in workforce strength in all areas, including distribution. This study aims to collect and present workforce data that distributor companies can use to create an attractive company culture to strengthen their workforce. This study collected data via survey and analyzed current workforce satisfaction, attraction, retention factors, and demographics in the roofing industry. Findings yield that the overall work and the yearly compensation were key factors for attraction and retention. The study results illustrate the development of workforce needs in the affordability of benefits and career path. The importance of this study lies in the ability of distributor companies to understand areas they are doing well in and identify areas that need to be improved and incorporate the findings in developing recruitment material for new employees.